Structural and elemental characterization of glass and ceramic particles for bone surgery - Sirkiä, Saara (My University, 2021)
Objectives. Clinically used bioceramics have been characterized previously with different kinds of methods and comparison of results have proven to be difficult due to varieties of the material properties of interest. Therefore, in this study we compared clinically commonly used bioceramics of hydroxyapatite and carbonate apatite, two bioactive glasses 45S5 and S53P4, and alumina with respect of properties which according to the present knowledge are significant for bone biology. Methods. Physicochemical properties of the materials were characterized by various methods. Attenuated Total Reflectance Fourier Transform Infrared (ATR-FTIR) was used to analyze the material vibrational features. X-ray Power Diffraction (XRD) was used to characterize the material crystal structure and scanning electron microscopy-energy-dispersive x-ray analysis (SEM-EDXA) was used to evaluate the morphology and size of the materials and to calculate their oxide content. The dissolution behavior of the materials, ion release and pH changes in Tris buffer in a continuous flow-through reaction for 24-hours were determined. The change of the surface of the bioactive glasses by interfacial reaction during the Tris immersion was examined and the thickness of the surface reaction layer of the materials was studied. Results. SEM examination showed that the particle morphology of BG 45S5, BG S53P4 and alumina particle´s surface was smooth. The surface of HAP was porous, but also CAP showed some surface porosity. An increase in the pH of the immersion solution was observed especially for BG 45S5 and BG S53P4. HAP, CAP and alumina caused only a minor increase in pH. BGs 45S5 and S53P4 showed a rapid initial release of sodium and calcium ions, followed by the release of silicon species. Minor release of sodium ions was registered for HAP, CAP and alumina. Calcium ion release was low but constant over the experimental time while only a minor initial dissolution was measured for HAP. Significance. The in vitro study showed differences in the materials’ properties, which are considered to be important for biological suitability and in clinical applications, such as materials tomography, ion release and pH changes.

Kliinisessä käytössä olevista biokeraameista on julkaistu monia tutkimuksia, mutta tutkimustulosten vertailu on vaikeaa johtuen tutkimuksien erilaisesta tutkimuskoeasettelusta ja tutkituista materiaalien ominaisuuksista. Tässä tutkimuksessa vertailtiin viittä kliinisessä käytössä olevaa biomateriaalia: hydroksiapatiittiä (HAP), karbonoitua apatiittiä (CAP), kahta biolasia 45S5 ja S53P4, sekä alumiinioksidia. Materiaalien fysikaaliskemialliset ominaisuudet karakterisoitiin erilaisia menetelmiä käyttäen: ATR-FTIR- spektroskopialla (Attenuated Total Reflectance Fourier Transform Infrared) tutkittiin materiaalien molekyylien väliset sidokset, röntgenkristallografian (X-ray Power Diffraction) avulla tutkittiin materiaalien kolmiulotteiden rakenne ja kiteisyys ja SEM-EDXA (Scanning Electron Microscopy-Energy-Dispersive X-ray Analysis) menetelmän avulla karakterisoitiin biomateriaalipartikkelien morfologia ja koko, sekä laskettiin materiaalien oksidipitoisuudet. Materiaalien liukoisuusominaisuudet määritettiin kvantifioimalla ja kvalifioimalla materiaalista vapautuvien ionien määrä ja mittaamalla pH-arvon muutokset TRIS-puskurissa jatkuvan läpivirtauksen systeemissä 24 tunnin ajan. Materiaalien pinnan muutokset edellä mainitussa systeemissä tutkittiin SEM-EDXA-menetelmällä ja reaktiokerroksen paksuus määritettiin materiaaleista. SEM-kuvat näyttivät biolasipartikkelien 45S5 ja S53P4 sekä alumiinioksidipartikkelien pinnan olevan sileä, kun taas hydroksiapatiitin ja karbonoidun apatiitin pinta oli huokoinen. pH-arvo nousi erityisesti biolasien S53P4 ja 45S5 kohdalla, toisin kuin CAP-, HAP- ja alumiinioksidimateriaaleilla havaittiin vain pieni pH-arvon nousu. Biolaseilla 45S5 ja S53P4 havaittiin kokeen alussa nopea natrium- ja kalsiumionien liukeneminen, jonka jälkeen materiaaleista liukeni pii-ioneita. Pientä natriumionien liukenemista havaittiin myös HAP-, CAP- ja alumiinioksidimateriaaleilla. Edellä mainituilla materiaaleilla kalsiumionien vapautuminen oli matalaa koko kokeen aikana, vain pienintä liukenemista havaittiin HAP:lla. In vitro kokeet osoittivat eroavaisuutta materiaalien ominaisuuksien välillä. Tutkitut materiaalien ominaisuudet, kuten pinnan ominaisuudet, ionien vapautuminen ja pH-arvon muutos ovat tärkeitä ominaisuuksia tutkittaessa materiaalien biologista yhteensopivuutta sekä sovellettaessa materiaaleja kliiniseen käyttöön.
Keywords: bioceramics, bioactive glass, bioglass, ion-release, physicochemical properties, characterization